AHP-based risk analysis of energy performance contracting projects in Russia. (October 2016) - Garbuzova-Schlifter, Maria; Madlener, Reinhard
Abstract: Understanding and properly managing risks that could potentially affect the target- and performance-based profits of energy performance contracting (EPC) projects are essential. It is particularly important for the establishment and success of energy service companies (ESCOs) acting in the vulnerable environment of the vast but highly energy-inefficient Russian market. This study systematically explores common risk factors and causes of risk associated with EPC projects executed in three Russian sectors: (1) industrial; (2) housing and communal services; and (3) public. Several interviews with the Russian EPC experts were accomplished and a qualitative risk assessment by using an analytic hierarchy process (AHP) approach. The data were obtained from a web-based questionnaire survey conducted among Russian EPC project executors. For each focus sector, a specific preference-based ranking of the identified risk factors and causes of risk was derived. The AHP results show that causes of risk related to the financial and regulatory aspects contribute most to the riskiness of EPC projects performed in all three focus sectors in Russia, calling for the special attention of EPC policy- and business-makers. Due to sectorial particularities and different actors involved, we conclude that there is a need for elaboration of sector-specific contractual schemes for EPC projects. Highlights: AHP- and survey-based study of energy performance contracting (EPC) projects in Russia. Main risk factors and causes of risk associated with EPC projects are investigated. In practice, lack of a feasible risk management approach in EPC projects. Regulatory and financial risks contribute most to the EPC projects' riskiness. Elaboration of the sector-specific EPC project contractual scheme is required.